Biochemical and genetic mechanisms used by plant growth promoting bacteria - Glick, Bernard R. (Imperial College Press, 1999)
This book is intended for a wide range of individuals, including scientists, students and informed laypersons who are interested in agricultural biotechnology, alternative agriculture, bioremediation of the environment and decreasing our reliance on pesticides and fungicides. It will deal primarily with understanding, at a biochemical and molecular biological level, how certain free living bacteria are able to promote plant growth; symbiotic bacteria such as Rhizobia will be mentioned only briefly. The assumption underlying the entire endeavour will be that a more profound understanding of these fundamental mechanisms will eventually permit scientists to manipulate these bacteria and use them more efficiently as a regular component of agricultural and/or horticultural practice. Therefore, while all the topics are discussed in as comprehensive a manner as possible, the book emphasizes a critical overview of the field rather than a mere compendium of data.